Embedded: a systems librarian's experience in Afghanistan. Issue 6 (12th August 2019) - Kovalcik, Justin D.
Abstract : Purpose: The purpose of this paper is to present the experience of a systems librarian deployed to Afghanistan as an academic advisor from the US Military Academy, West Point. While discussing tasks and challenges faced, the author provides accounts of events that shaped and strengthened professional lessons learned as the first library academic advisor to the National Military Academy of Afghanistan (NMAA). The focus of the paper emphasizes the importance of listening, collaborating, leadership, immersion and integration of disparate teams into a cohesive unit. Design/methodology/approach: Utilizing summaries of daily events taken during a six-month deployment along with relevant research on library's in developing countries and embedded librarianship, this paper provides an overview of the projects, challenges and relationships necessary to become successfully embedded. Findings: Integration into various aspects of NMAA and the advisor team leads to successful project outcomes and greater relevance of the library in the academy. Practical implications: Administrators and librarians will be able to review the experience and professional lessons learned of an embedded librarian into a foreign environment and team. Originality/value: In addition to providing unique perspectives involving embedded librarianship, this paper addresses topics of leadership, team cohesion and influence.